2017
DOI: 10.1039/c6fo01360k
|View full text |Cite
|
Sign up to set email alerts
|

Anti-glycation and anti-oxidative effects of a phenolic-enriched maple syrup extract and its protective effects on normal human colon cells

Abstract: Oxidative stress and free radical generation accelerate the formation of advanced glycation endproducts (AGEs) which are linked to several chronic diseases. Published data suggest that phenolic-rich plant foods, show promise as natural anti-AGEs agents due to their anti-oxidation capacities. A phenolic-enriched maple syrup extract (MSX) has previously been reported to show anti-inflammatory and neuroprotective effects but its anti-AGE effects remain unknown. Therefore, herein, we investigated the anti-glycatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…MSX (12.5, 25, and 50 μg/mL) reduced H 2 O 2 ‐ and MGO‐induced ROS production by 44.4%, 59.0%, and 69.4%, and 34.9%, 51.3%, and 56.6%, respectively, as compared to the model group (Figure 2). This is in agreement with our previously reported studies showing that MSX exerts cytoprotective effects by attenuating cellular ROS in normal human colon CCD‐18Co cells 13 and murine microglial BV‐2 cells ( 15,16 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…MSX (12.5, 25, and 50 μg/mL) reduced H 2 O 2 ‐ and MGO‐induced ROS production by 44.4%, 59.0%, and 69.4%, and 34.9%, 51.3%, and 56.6%, respectively, as compared to the model group (Figure 2). This is in agreement with our previously reported studies showing that MSX exerts cytoprotective effects by attenuating cellular ROS in normal human colon CCD‐18Co cells 13 and murine microglial BV‐2 cells ( 15,16 ).…”
Section: Resultssupporting
confidence: 93%
“…Among these natural products, we reported that phenolic‐enriched extracts of pomegranate fruit ( Punica granatum ) and red maple leaves ( Acer rubrum ) showed potent inhibitory effects against AGEs formation and protected human keratinocytes against oxidative stress induced cytotoxicity ( 12,15,16,21 ). In addition, we also reported that a polyphenol‐enriched maple syrup extract (MSX) showed inhibitory activity against AGEs formation and protective effects against AGEs‐ and MGO‐induced cytotoxicity in normal human colon cells 13 . MSX has also been reported to show a diverse range of biological activities including antioxidant, antidiabetic, anti‐inflammatory, and anti‐neuroinflammatory effects ( 13,15,16,22,23 ) but its skin protective effects in human keratinocytes remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A number of plant derived compounds showed hypoglycemic properties (Sefi, Fetoui, Makni, & Zeghal, ) such total phenols, flavonoids, terpenoids, and coumarins; reducing glucose levels and increasing the insulin amounts in plasma (Santosh Tupe et al, ). In point of fact, several studies have noted the capacity of phenolic compounds (PC) to inhibit AGEs (Ah Jung et al, ); mainly flavonoids (Liu et al, ). It is also interesting to point out that PC present the ability to scavenge reactive carbonyls through the formation of adducts with them (Wang, Yagiz, Buran, Do Nascimento Nunes, & Gu, ) and show a reducing activity of free radicals contributing to the inhibition of glycation (Adisakwattana et al, ; Ramkissoon, Mahomoodally, Ahmed, & Subratty, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, these drugs demonstrate significant side effects, including weight gain and gastrointestinal distress. Therefore, finding new potential natural products that prevent DM is necessary [4]. Phenolic compounds are important secondary plant metabolites that determine the sensory and nutritional qualities of fruits, vegetables, and other plant products.…”
Section: Introductionmentioning
confidence: 99%